Comparison of the Effectiveness of Discovery Learning and Direct Instruction Models in Physical Education Learning Basketball Material - Sahabuddin, Sahabuddin; Sudirman, Sudirman (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aims to analyze and compare the effectiveness of the Discovery Learning and Direct Instruction models in improving basic basketball technical skills in students at SMA Negeri 5 Makassar. This study used a quasi-experimental design with a pretest–posttest control group. The sample size was 40 students divided into two groups: an experimental group receiving the Discovery Learning model and a control group receiving Direct Instruction. The research instrument included a basic basketball technical test covering passing, dribbling, and shooting. Data were analyzed using descriptive and inferential statistics, including prerequisite tests, paired sample t-tests, independent t-tests, and gain score calculations. The results showed that both learning models significantly improved students’ basic technical skills. However, the Discovery Learning group showed a higher gain score of 26.20 (56.2%) compared to the Direct Instruction group, which had a gain score of 17.30 (37.7%). Discovery-based learning provides a more meaningful learning experience, enhancing movement creativity, conceptual understanding, and active student participation. Conversely, Direct Instruction remains effective but tends to be more mechanistic and less exploratory. In conclusion, Discovery Learning is more effective when applied to physical education (PJOK) basketball. Teachers are advised to consistently integrate this model, but still combine it with Direct Instruction to provide a strong technical foundation. Further research is needed to examine its long-term impact and applicability to other sports materials or contexts.